HUBUNGAN ANTARA KECERDASAN EMOSIONAL DENGAN PRESTASI BELAJAR PADA SISWA KELAS II SMK KESEHATAN BHAKTI KENCANA TASIKMALAYA - Lestanti Mukodri, Dewi Mey (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Data result from speaking with teachers in senior vocational school of bhakti kencana tasikmalaya about students conditions from 6 teachers is one teacher said almost come late when beginning study, three teachers said that students don’t care when teachers is teaching and two teachers said that many students do not finishing home work when they gated it. The destination this observating is knowing relationship between emotional quotient with achievement study in students second class senior vocational school of bhakti kencana tasikmalaya. The population this observating is all of students class senior vocational school of bhakti kencana tasikmalaya amount of 111 students. The result observating is there is relationship between emotional quotient with achievement study in students class senior vocational school of bhakti kencana tasikmalaya from P Value (0.000) less than α (0.05). this level is medium category and OR Value is 17.862 that have meaning students who has emotional smart not good have risk 17.862 times not good achievement than students who has emotional quotient with good category. With the results there is relationship between emotional quotient with achievement study is hoped to giving experience about goodness from emotional quotient such as knowing individual emotional, operating emotional, motivating their selves, and empaty so achievement students second class senior vocational school of bhakti kencana tasikmalaya from their value with limit 7.5. Keyword : Emotional Quotient, Achievement Study